Assessment of Ipsilateral Efferent Effects in Human via ECochG - Verschooten, Eric; Strickland, Elizabeth A.; Verhaert, Nicolas; Joris, Philip X. (Frontiers in Neuroscience, 2017)
Development of electrophysiological means to assess the medial olivocochlear (MOC) system in humans is important to further our understanding of the function of that system and for the refinement and validation of psychoacoustical and otoacoustic emission methods which are thought to probe the MOC. Based on measurements in anesthetized animals it has been hypothesized that the MOC-reflex (MOCR) can enhance the response to signals in noise, and several lines of evidence support such a role in humans. A difficulty in these studies is the isolation of efferent effects. Efferent activation can be triggered by acoustic stimulation of the contralateral or ipsilateral ear, but ipsilateral stimulation is thought to be more effective. However, ipsilateral stimulation complicates interpretation of effects since these sounds can affect the perception of other ipsilateral sounds by mechanisms not involving olivocochlear efferents. We assessed the ipsilaterally evoked MOCR in human using a transtympanic procedure to record mass-potentials from the cochlear promontory or the niche of the round window. Averaged compound action potential (CAP) responses to masked probe tones of 4 kHz with and without a precursor (designed to activate the MOCR but not the stapedius reflex) were extracted with a polarity alternating paradigm. The masker was either a simultaneous narrow band noise masker or a short (20-ms) tonal ON- or OFF-frequency forward masker. The subjects were screened for normal hearing (audiogram, tympanogram, threshold stapedius reflex) and psychoacoustically tested for the presence of a precursor effect. We observed a clear reduction of CAP amplitude by the precursor, for different masking conditions. Even without an MOCR, this is expected because the precursor will affect the response to subsequent stimuli via neural adaptation. To determine whether the precursor also activated the efferent system, we measured the CAP over a range of masker levels, with or without precursor, and for different types of masker. The results show CAP reduction consistent with the type of gain reduction caused by the MOCR. These results generally support psychoacoustical paradigms designed to probe the efferent system as indeed activating the MOCR system, but not all observations are consistent with this mechanism.